The problems that faced the profession of pearl diving in Sharjah - alsuwaidi, marwa mohamed; Benkheira, Nadjib (Al-Adab Journal, 2022)
The profession of pearl diving and searching for it is the most prominent profession in the Arabian Gulf region in the pre-oil era. The profession of pearl diving had a great impact on economic development, which the Emirate of Sharjah and the UAE in general lived through, where the profession of pearl diving remained. The profession is the most widespread in the Emirate of Sharjah and the rest of the Emirates on the Gulf coast, due to the treasures that the Arabian Gulf contains in its interior, but this profession has faced many difficulties that have led to its disappearance and the reluctance of the people of the emirate to it because of its great hardships and dangers, and one of the most prominent of these was Risks; The emergence of so-called "cultured pearls" or "artificial pearls", which began to compete with the strength of natural pearls in the global markets, in addition to the outbreak of the First World War and the economic measures that followed that affected the pearl trade, as well as the great economic development that appeared in the Emirate of Sharjah and the Emirates The United Arab Emirates, and all the Gulf countries as a result of the emergence of oil and natural gas, which negatively affected this trade, which led to the extinction of its era and made it into oblivion.